Challenges and Successes of Interprofessional Health Education. (26th June 2020) - Mitchell, Anne Bradley; Ankam, Nethra; Umland, Elena; Earland, Tracey Vause; Dallas, Sarah; Ukanna, Aniekan
Abstract: This chapter explores the development of the Jefferson Health Mentors Program over the past decade and the challenges and solutions to continue to provide a relevant interprofessional curriculum.